Estimation of Geometric Factors for the Particle Detecting Instruments of the Geostationary Satellite GK2A at 128.2°E Longitude Based on Observations of the Outer Radiation Belt During Geomagnetically Quiet Periods. Issue 1 (23rd January 2023) - Seol, W.‐H.; Lee, C.‐H.; Seon, J.; Shin, Y.‐C.; Kim, K.‐H.; Larson, D. E.; Parks, G. K.; Sample, J.
Abstract: We present a method to determine energy‐dependent geometric factors for charged particle instruments in electron energy range of 125–2, 200 keV aboard the geostationary satellite GEO‐KOMPSAT‐2A (GK2A), stationed at 128.2°E longitude. As deduced from the GEANT4 Monte Carlo simulation, the response function of the instrument in a matrix form was employed to undertake forward‐fitting of the differential energy spectra against various functions such as the double Maxwellian (DM), relativistic kappa (KP), and power‐law (PL). Thereby, we determined the energy‐dependent geometric factors for each energy channel and instrument. The forward‐fitting method was performed for a selected period of geomagnetically quiet days from May to November 2019, by applying stringent conditions to geomagnetic indices and the residual from the fit. It was found that the KP and DM functions provided better fits overall, whereas the PL function yielded considerably worse fits to the measurements. For the KP and DM functions, the validity of the geometric factors was examined against the distributions of the measured count rates and inferred model fluxes. The estimated model parameters, such as the spectral index from the KP function or the temperature from the DM functions, were also analyzed. The present study shows that the instruments provided quantitative observations of the outer radiation belt at a vantage point of 128.2°E longitude and allowed for a simple and reliable means to obtain electron fluxes based on combinations of results from numerical simulation, ground calibration, and space measurements. Plain Language Summary: Measurements in the outer radiation belt from modern instruments often consist of count rates over energy bins. The conversion of the measurements to a more physically meaningful quantity of energy distributions requires a physical model that attempts to account for complex observations with few physical parameters. By applying a stringent set of conditions to the geomagnetic indices and the residuals from the fit, we tested models of electron energy distribution in the outer radiation belt when the Earth's magnetosphere was presumably in a quiet state. This suggests the possibility of good modeling of the energy distribution using simple mathematical functions. Based on the results, a simple scale factor was derived that enables the conversion of the count rates into the energy distributions. Using this scale factor, complex nonlinear calculations leading to tolerable inaccuracies in the results can be avoided. The analysis shows that the quiet electron radiation belts are well described with kappa or double Maxwellian functions and that a reasonably good conversion is possible with a simple scale factor. The data presented here at a vantage point of geostationary orbit are complementary to existing observations, allowing for quantitative space weather research over a wider range of local times. Key Points: Analysis of observations from charged particle instruments aboard the GK2A geostationary satellite during a geomagnetic storm in May 2019 Models of electron differential fluxes examined using different functions and the goodness‐of‐fit estimated for each model Construction of geometric factors based on forward fitting of flight data over geomagnetically quiet days in 2019